Karakteristik dan Aplikasi Aliran Romantisme Arab - Najib, Emha Aenun (Universitas Ahmad Dahlan, 2021)
Al-Masa poetry is the work of a famous Egyptian poet named Khalil Mutran. Khalil Mutran (1872-1949) is recorded as one of Egypt's last neo-classical poets. One of his works is the poem Al-zaman, the poem al-masa telling about the suffering of the figure both physical suffering. Meanwhile, the flow of romanticism is a village literary genre that emerged after the flow of classicism which is commonly called the urban literary genre. The purpose of this research is to find out the historical flow of romanticism and its application in the literary work of the poetry of al-zaman Karta Khail Mutran. The method used in this research is descriptive qualitative research method. The results of this study indicate that al-Masa's poetry contains elements of romance. That contains elements of Return to nature, melancholy, primitivism, sentimentalism, individualism and exoticism.